Factors Hindering Employees’ willingness to Accept Expatriation: A Survey in Chinese MNCs - MEI, JIA (2019)
Expatriation willingness can be regarded as a critical predictor for successful global assignments in MNCs. However, previous surveys reveal low expatriate willing remains a tricky issue to select suitable candidates for international assignments. Relevant studies on expatriate willing mainly focused on western-developed countries such as the US and Germany with rich experience while little in developing areas. Hence, this research is intended to explore the potential factors resulting in low expatriate willing in developing China that has a growing demand for overseas assignments.